Hubungan Antara Tingkat Kebutuhan Konsumsi Informasi dan Kualitas Isi Media Dengan Loyalitas Pembaca (Studi Pada Harian Meteor Terkait Perubahan Dari Koran Kuning ke Koran Umum) - Ariyanti, Aning Karindra (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2012)
Abstract Declining reader loyalty Meteor Daily Newspaper as a conceptual change from white to a public newspaper circulation figures indicated a decrease in the background of this research. The aim of research to find out the relationship between the level of information consumption needs with loyalty readers; to know the relationship between the quality of media content with reader loyalty, as well as to know the relationship between the level of consumption needs and quality of media content information with the loyalty of readers of Meteor Daily Newspapers in Semarang. Results showed that most respondents have considered the information consumption needs in the low category. Level of consumption is positively related information with the loyalty of readers at the Meteor Daily Newspaper. Most respondents also rated the quality of media content Meteor Daily Newspaper falls within either category. The quality of media content are positively related to loyalty to the reader to the Daily Meteor. While the level of information consumption needs and quality of media content are positively related to loyalty to the reader to the Meteor Daily Newspaper. Â Keywords : consumption needs information, media content quality, loyalty readers.